Analisa Risiko K3 di Jalan Tol - Adinda Adinda; Adelina Fitry R Lubis; Rahmi Indah Syahrina Nasution; Abdurrozzaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
Occupational safety and health (K3) is one aspect of labour protection that is crucial for raising business productivity. In order to create a just and prosperous society defines occupational safety and health as the ideas and actions taken to guarantee the integrity and perfection, both physical and spiritual, of the workforce in particular and of people in general. This study employs a literature review methodology that centers on factors or subjects examined in earlier studies. A literature review requires gathering information from documents and libraries. Research publications and literature studies provided data for the K3 analysis of toll roads. Articles are gathered by searching literature sources using preset inclusion criteria, which are entire scientific publications published during the last five years. Google Scholar can be searched using the following keywords to find review literature sources: K3 Risk Management for Cisumdawu Phase III Toll Road Works. Employers need to be mindful of occupational health. An effective occupational health program will benefit workers greatly because workers will be away from work less frequently due to illnesses contracted by coworkers or other individuals.